KAJIAN KONSUMSI BAHAN BAKAR KENDARAAN BERMOTOR DI JAKARTA, SURABAYA DAN YOGYAKARTA - STYAWAN, BRAM; Sopha, Bertha Maya ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the society that has high level of mobility rates , the transportation needs is essential for the survival activity . Transportation activities always related to fuel consumption, oil as a transportation fuel is a form of renewable energy that can not be renewable. The number of oil needs are not proportional to the number of it's production, this situation make the government to import the amount of oil from abroad. The increasing of vehicle numbers can cause the increasing of fuel consumption. Beside the increasing of vehicle numbers, the driving behavior, the properties and adjusted to vehicle and the transportation conditions allegedly having a large correlation in vehicle fuel consumption. The purpose of this research was 1 ) to identify the explainated factors that correlate to the vehicle fuel consumption in three cities in Indonesia , 2 ) to model the equations of parameters that correlate to vehicle fuel consumption, 3 ) to give some alternative solutions to consumption fuel vehicles based on the parameter. This research used correlation and regression analysis approach to determine the relationship of fuel consumption and related factors.dfdsffsdfsdfsfsfs The results showed that the large consumption of automobiles in the city of Jakarta, Surabaya and Yogyakarta tend to be associated to the age of vehicle, the ingestion volume of vehicle, the driver speeds, the engine heats habits, the driving mileage, the number of passenger, the habit of pulling the gear position gas irregular due to potholes or speed limiting devices. The consumption of motor in the city of Jakarta, Surabaya and Yogyakarta tend to be associated with the age of rider, the income of rider, the age of vehicle, the driving speed, the driving distance, the number of passenger, the frequency of regular maintenance of vehicles, the habit gas plays or the habit pulling gas does not irregular due to congestion.